2004
DOI: 10.1001/archpedi.158.4.353
|View full text |Cite
|
Sign up to set email alerts
|

Parental Report of Outdoor Playtime as a Measure of Physical Activity in Preschool-aged Children

Abstract: Parental-report measures of outdoor playtime were significantly correlated to a direct measure of physical activity in preschool-aged children, and are worthy of future evaluation as a survey measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
291
7
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(316 citation statements)
references
References 10 publications
8
291
7
10
Order By: Relevance
“…Consistently, Klesges et al (1990) reported a correlation coefficient of 0.34 between outdoor time and physical activity in pre-schoolers. Similar correlations have been found by Burdette et al (2004). Correlations might be to some extent lower in GerES IV, as this sample includes children up to 14 years of age.…”
Section: Outdoor Time Physical Activity and Overweightsupporting
confidence: 78%
See 1 more Smart Citation
“…Consistently, Klesges et al (1990) reported a correlation coefficient of 0.34 between outdoor time and physical activity in pre-schoolers. Similar correlations have been found by Burdette et al (2004). Correlations might be to some extent lower in GerES IV, as this sample includes children up to 14 years of age.…”
Section: Outdoor Time Physical Activity and Overweightsupporting
confidence: 78%
“…Concerning measuring time-location information, GerES IV relied on retrospective survey questions as did many other studies (e. g. Villarreal-Calderón et al 2002;Burdette et al 2004;Brasche & Bischof 2005). KiGGS and GerES IV involved detailed medical examinations, extensive interviews on various topics, and investigations in the participant's homes.…”
mentioning
confidence: 99%
“…28 In addition, the underlying differences between indoor and outdoor activities could influence the association with BP differently. Although studies have shown that outdoor physical activity among children is associated with higher physical activity, 29,30 no study to date has examined the differences in the level of energy expenditure between indoor and outdoor activities among prepubertal children. Potentially, the underlying differences in the intensity of participating in indoor and outdoor activities could differentially influence systolic and diastolic BP.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument containing 38 closed questions was constructed by adapting the questionnaire proposed by the team responsible for the project "Study of Childhood Obesity in Florianópolis" 18 . The adjustments made included the review of question wording, which went from a self-report format to face-to-face interview, and the inclusion of a section related to the physical activity measurement of the instrument proposed by Burdette et al 19 . The interviews were answered only by the father or the mother of the selected children.…”
Section: Schoolmentioning
confidence: 99%
“…Validity of the instrument used specifically for obtaining measurements of physical activity was tested against direct measurement of physical activity obtained through motion sensors 19 . Additionally, parents of 20 children (10 boys and e 10 girls) of a private school on the outskirts of the metropolitan area of Recife were interviewed individually in two separate occasions, one week apart.…”
Section: Schoolmentioning
confidence: 99%